DEVELOPMENT OF SPEED INFORMATION HARDWARE SOFTWARE (SHICEPATS) TO SUPPORT MOTOR LEARNING ASSESSMENT OF MADRASAH IBTIDAIYAH STUDENTS - Adi Wijayanto; Muhamad Zaini; Barsihanor Barsihanor; Rania Lampou; Mona Refaat Taman; Raveenthiran Vivekanantharasa; Cris T. Zita (PD PGMI se Indonesia, 2025)
In the context of Physical Education learning, objective and reliable speed assessment is essential not only for measuring students’ physical abilities but also for informing instructional strategies, individualized feedback, and fair evaluation of learning outcomes. The absence of standardized and objective measurement tools can hinder teachers’ ability to monitor student progress, design appropriate learning interventions, and motivate students effectively. From the background above, the following problem formulations can be taken: 1) What is the range of sports speed norms for students?, 2) What is the development model for sprint speed information hardware software (SHICEPATS) for tests and evaluations of state Islamic higher education students based on ESP8266 wireless?, 3) What is the feasibility of sprint speed information hardware software (SHICEPATS)?. The process that must be passed through in research and development by Borg and Gall. Feedback from the sports science validator highlighted several weaknesses in SHICEPATS, prompting important product improvements. One key suggestion was the creation of a comprehensive user manual to guide users through the device's operation. Based on input from IT experts regarding the control unit box, the researchers redesigned it to ensure a unique and distinctive appearance that distinguishes. The results of the small group trial showed that 38.10% were still unable to perform digital sprint tests and measurements because the operational method was not yet user friendly and there were still many displays that were confusing. The use of SHICEPATS in the large group trial has improved, the level of ease of performing measurement tests and reading results was 83.21%. In general, the level of ease of SHICEPATS design and ease of carrying was 91.97%, these results indicate that users find it much easier to process and understand the data generated by the device. The system is designed to calculate sprint speed using two strategically placed sensors.